2002
DOI: 10.1021/jm020918w
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Agents. 2. Synthesis, Structure−Activity Relationships, and Biological Evaluation of Substituted 5H-Pyridophenoxazin-5-ones with Potent Antiproliferative Activity

Abstract: New antiproliferative compounds, 5H-pyrido[3,2-a]phenoxazin-5-ones (1-10), 5H-benzophenoxazin-5-one (11), 5H-pyrido[2,3-a]phenoxazin-5-one (12), 5H-pyrido[3,4-a]phenoxazin-5-one (13), and 5H-pyrido[4,3-a]phenoxazin-5-one (14), were synthesized and evaluated against representative human neoplastic cell lines. The excellent cytotoxic activity of these polycyclic phenoxazinones, structurally related to the actinomycin chromophore, is discussed in terms of structural changes made to rings A and D (Chart 1). Electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 12 publications
3
57
0
Order By: Relevance
“…The specific role of the bioactivity of pyridine ring has been recognized and the introduction of some pyridine analogs into the molecules of drugs could result in new compounds that have significant biological activity compared with the parent compounds Straub et al, 1997;Bolognese et al, 2002;Tiwari et al, 2002;Kuo et al, 2005). It was also reported that a diverse array of naturally occurring alkaloids in sponges exhibit potent bioactivities because of the presence of a pyridine moiety (Vincent et al, 1997;Gordon et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The specific role of the bioactivity of pyridine ring has been recognized and the introduction of some pyridine analogs into the molecules of drugs could result in new compounds that have significant biological activity compared with the parent compounds Straub et al, 1997;Bolognese et al, 2002;Tiwari et al, 2002;Kuo et al, 2005). It was also reported that a diverse array of naturally occurring alkaloids in sponges exhibit potent bioactivities because of the presence of a pyridine moiety (Vincent et al, 1997;Gordon et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the dimethyl derivatives 1 and 2 displayed an enhanced specificity toward some tumor cell lines compared with the corresponding monomethylated analogues previously described. 10 Compound 2 revealed a distinct specificity toward two lymphoma/leukemia cells, CD4 + acute T-lymphoblastic leukemia (C8166) and acute B-lymphoblastic leukemia (CCRF-SB) as well as two carcinoma cells, colon adenocarcinoma (HT-29) and nasopharyngeal carcinoma (KB). Compound 5 exhibited specificity against 5637 carcinoma cells and MT-4 leukemia cells.…”
Section: Resultsmentioning
confidence: 99%
“…They possess various biological activities such as antimicrobial [3], hypolipidacmic [4], antidiabetic [5], anti-inflammatory [6], antimycobacterial [7], antithrombotic [8], antagonism to progesterone receptor [9], antitumor [10], antiviral [11], leucocyte clastase [12] and scrotonin reuptakes [13]. The ground state equilibration of organic compounds was established using spectroscopic data [14].…”
Section: Intrductionmentioning
confidence: 99%